2009
DOI: 10.1111/j.1530-0277.2009.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide S Receptor Gene Expression in Alcohol Withdrawal and Protracted Abstinence in Postdependent Rats

Abstract: Background: Alcoholism is a chronic disease characterized by frequent intoxications followed by withdrawal episodes and relapse to alcohol use. Neuroplastic changes associated with these intoxication and withdrawal cycles are thought to play a key role in disease progression. Recently, it has been shown that neuropeptide S (NPS), a newly deorphanized neuropeptide receptor system, facilitates relapse to alcohol seeking in laboratory animals. Given that a history of ethanol intoxication may increase vulnerabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…Recently, pathophysiology and etiology of acute alcohol intoxication through experimental practice on rodent models have gotten much attention, among which rat models have been universally adopted to discover the influence of acute alcohol intoxication on the central nervous system (CNS) [8,9]. Abundant rat models of acute alcohol intoxication have shown that acute alcohol intoxication may stimulate genetic expression of neural cells of the cerebellum, which may take significant part in the prognosis and treatment of CNS lesions [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pathophysiology and etiology of acute alcohol intoxication through experimental practice on rodent models have gotten much attention, among which rat models have been universally adopted to discover the influence of acute alcohol intoxication on the central nervous system (CNS) [8,9]. Abundant rat models of acute alcohol intoxication have shown that acute alcohol intoxication may stimulate genetic expression of neural cells of the cerebellum, which may take significant part in the prognosis and treatment of CNS lesions [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by a recent study that demonstrated that chronic exposure to high levels of EtOH combined with a period of abstinence led to a significant upregulation of NPSR mRNA levels, both after acute EtOH withdrawal and after prolonged abstinence, in several brain regionsFincluding the BLA (Ruggeri et al, 2010). However, an increased NPS effect on mood may also reflect a change in neuronal excitability or neural network function in response to chronic EtOH consumption, unrelated to NPSR levels per se, that make the neuron/system more sensitive to NPSR activation.…”
Section: Discussionsupporting
confidence: 70%
“…These observations suggest that NPS may play an important role in learning and memory. Other studies have produced evidence for a role of central NPS neurotransmission in reward and drug abuse (Badia-Elder et al, 2008;Canella et al, 2009;Pañeda et al, 2009;Ruggeri et al, 2010). Finally, we have recently described antipsychotic effects of NPS in animal models of pharmacologically induced psychosis (Okamura et al, 2010) and a possible genetic association of NPSR genotypes with panic disorder (Okamura et al, 2007).…”
mentioning
confidence: 89%